2011
DOI: 10.4317/jced.3.e424
|View full text |Cite
|
Sign up to set email alerts
|

Non-surgical management of chronic periodontitis with two local drug delivery agents-A comparative study

Abstract: Background: The selective removal or inhibition of pathogenic microbes with locally delivered antimicrobials when combined with scaling and root planing is often an effective approach for the managment of chronic periodontitis. Aim: To compare the clinical efficacy of tetracycline fibers and a xanthan based chlorhexidine gel in the treatment of chronic periodontitis. Methods and materials: Thirty systemically healthy patients in the age group of 30-50 years suffering from generalized chronic moderate periodont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…This reduction in supragingival plaque score could be attributed to chemical control of subgingival plaque by tetracycline fibers, which could also have an inhibitory effect on supragingival plaque. [23] Similar observations were made by Friesen et al, (2002). [11] Significant reduction in PI reduction was seen in chlorhexidine group and control group at 1 month and 3 months.…”
Section: Pisupporting
confidence: 70%
“…This reduction in supragingival plaque score could be attributed to chemical control of subgingival plaque by tetracycline fibers, which could also have an inhibitory effect on supragingival plaque. [23] Similar observations were made by Friesen et al, (2002). [11] Significant reduction in PI reduction was seen in chlorhexidine group and control group at 1 month and 3 months.…”
Section: Pisupporting
confidence: 70%
“…Various studies have reported that local treatment with Periodontal Plus AB showed significant gain in CAL and reduction in probing depths compared to the control group [23][24][25][26]. The inter-comparison of clinical efficacy between TET-fibres and a xanthan based CHX gel (Chlosite ® ) showed that TET-fibres were better (they had significant gain in CAL and reduction in probing depths) than CHX gel [27]. More favourable outcome in both the clinical and biochemical variables when SRD was combined with LDD of TET fibres -reduction in the Alpha-2-macroglobulin levels in GCF.…”
Section: Fibresmentioning
confidence: 99%
“…Although, an additional clinical benefit of adjuvant Page: 66 systemic antibiotics has been described, it is only recommended in cases of refractory or aggressive periodontics to prevent the development of antimicrobial resistance [35]. In earlier studies, it has been reported that the local delivery of adjuvant antimicrobial therapy is considered a safe and effective alternative to systemic administration [36,37,38]. In one of the studies, a non-surgical approach using the repeated intrasulcular application of tetracycline films and AgNPs was used.…”
Section: Antimicrobial Efficacy Of Silver Nanoparticles In the Treamementioning
confidence: 99%